Recalcitrance to transformation, a hindrance for genome editing of legumes - Nivya, V. M.; Shah, Jasmine M. (Frontiers in Genome Editing, 2023)
Plant genome editing, a recent method for targeted mutagenesis, has flourished as a promising tool for crop improvement and gene function studies. The last decade witnessed the genesis of many genome-edited plants such as rice, wheat, and tomato. As the preliminary steps in the procedure for genome editing involve genetic transformation, amenability to genome editing depends on the efficiency of genetic engineering. Hence there are more reports on the abovementioned crops because they are transformed with relative ease. Legume crops are rich in protein and thus are a favored source of plant proteins of the human diet in most countries.However, legume cultivation is often succumbed to various biotic/abiotic threats, thereby leading to high yield loss. Also, certain legumes like peanuts possess allergens and these need to be eliminated as these deprive many people from gaining the benefits of such crops. Further genetic variations are limited in certain legumes. Genome editing has the potential to offer solutions to not only combat biotic/abiotic stress, but also generate desirable knock-outs and genetic variants.However, except for soybean, alfalfa and Lotus japonicus, reports on genome editing of other legume crops are less. This is because except for the above three, transformation efficiency of most legumes is very low. Obtaining higher number of genome edited events is desirable as it offers the options to select genotypically/phenotypically best candidate, without the baggage of off-target mutations. Eliminating the barriers for genetic engineering would directly benefit in enhancing genome editing rates. Thus this review aims at comparing various legumes for their transformation, editing, and regeneration efficiencies, and discussing on various solutions available for increasing transformation and genome editing rates in legumes.